2008
DOI: 10.1186/2046-0481-61-4-233
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, work-home interference and burnout among Belgian veterinary practitioners

Abstract: There have been few formal studies on stress in veterinary surgeons and, in the rare studies available, stress is not examined jointly through the levels of job strain and job engagement, the sources of stress in the issue of work environment and the work-home interference. The authors' goal in this study was to analyse job engagement, job strain, burnout, work-home interference and job stress factors among 216 Belgian veterinary surgeons. Rural practice was compared to small animal and mixed activity. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 28 publications
3
65
0
5
Order By: Relevance
“…While life as a veterinary surgeon involves a broad skill set, clinical expertise with animals represents only one part, and participants voiced fears about being found 'lacking' in one (or several) respects of these idealised conceptions (Knights and Clarke, 2014). Part of the shock, articulated many times in our study, relates to the high demands and expectations of clients (Hansez et al, 2008), a significant source of stress where performance must be skilfully accomplished, persuasive and often privilege clients over animal patients.…”
Section: Competence As Accomplished Performancementioning
confidence: 99%
See 1 more Smart Citation
“…While life as a veterinary surgeon involves a broad skill set, clinical expertise with animals represents only one part, and participants voiced fears about being found 'lacking' in one (or several) respects of these idealised conceptions (Knights and Clarke, 2014). Part of the shock, articulated many times in our study, relates to the high demands and expectations of clients (Hansez et al, 2008), a significant source of stress where performance must be skilfully accomplished, persuasive and often privilege clients over animal patients.…”
Section: Competence As Accomplished Performancementioning
confidence: 99%
“…Much of the research is restricted to clinical pathology, technical advances, or sustaining injury from human-animal interactions (Hjorth and Roed-Peterson, 1980), and problems of mental health (Allister, 2015), addiction or suicide (Hansez et al, 2008;Bartram and Baldwin, 2010). A minority of studies has drawn attention to professional exclusivity and hierarchical/gendered status (Hamilton, 2013), the complexities of human-animal interactions (Enticott, 2012;Hamilton and Taylor, 2012), and regulatory anomalies (Hobson-West and Timmons, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bano and Jha reported that there were moderate levels of role stress among the employees in public and private sectors [18]. Moderate to high stress levels were observed among the Belgian veterinary surgeons [19]. Gardner and Hini also observed moderate stress levels among veterinarians [14].…”
Section: Discussionmentioning
confidence: 89%
“…It has been of large use for diagnosis purposes in diverse occupational fields (Bertrand et al, 2010;Hansez et al, 2007;Hansez & Chmiel, 2010;Hansez et al, 2008) and its two-dimensional structure has been validated and replicated (Barbier et al, 2009). The first aim of our study was to check if item wording has an impact on PNOSI structure.…”
Section: Discussionmentioning
confidence: 99%
“…The PNOSI has been of large use for diagnostic purposes in Frenchspeaking countries (especially Belgium and France), collecting more than 30,000 data from diverse occupational fields such as veterinary practice, farming, informatics, printing, pharmaceutics, and the energy, public or health care sectors (Bertrand, Peters, Perée & Hansez, 2010;Hansez, Bracci & Bertrand, 2007;Hansez & Chmiel, 2010;Hansez, Schins & Rollin, 2008). A recent study of Barbier, Peters & Hansez (2009) has confirmed the two-factor structure of the PNOSI.…”
Section: The Positive and Negative Occupational States Inventorymentioning
confidence: 99%